In Vitro Hypoglycemic, Hypolipidemic Activities and Antioxidant Capacity of Dark Tea and Pericarpium Citri Reticulatae Extract with Pericarpium Citri Reticulatae Volatile Oil - Zhitao PAN; Tingyu HUA; Xiaoyun WANG; Yi SHEN; Xunzhen ZHANG; Shaotong HUANG; Hanying DUAN; Chao WANG (Shipin gongye ke-ji)
Objective: Exploring the in vitro hypoglycemic, hypolipidemic and antioxidant activity of Pericarpium Citri Reticulatae volatile oil and dark tea/Pericarpium Citri Reticulatae extract. Methods: The volatile oil components of Pericarpium Citri Reticulatae were analyzed by gas chromatography-mass spectrometry (GC-MS), and then the effects of Pericarpium Citri Reticulatae, dark tea, dark tea with Pericarpium Citri Reticulatae extract and Pericarpium Citri Reticulatae volatile oil on in vitro α-glucosidase, pancreatic α-amylase, pancreatic lipase activity and the DPPH and ABTS+ free radicals scavenging capacity were studied with acarbose, orlistat and vitamin C (VC) as controls. Results: Limonene was the main component of Pericarpium Citri Reticulatae volatile oil, accounting for 62.89% of the total relative content. The inhibition rate of α-glucosidase of dark tea with Pericarpium Citri Reticulatae+volatile oil group (0.1 mg/mL) was 83.38%±1.82%, and the IC50 value was: acarbose<dark tea<dark tea with Pericarpium Citri Reticulatae+volatile oil<dark tea with Pericarpium Citri Reticulatae<Pericarpium Citri Reticulatae. The IC50 value of all groups on pancreatic lipase inhibition rate was in the range of 1.77~2.60 mg/mL. The DPPH free radical scavenging capacity of dark tea with Pericarpium Citri Reticulatae+volatile oil group at a concentration of 0.2 mg/mL was 94.85%±1.39%. The IC50 value of ABTS cation radical scavenging capacity was 27.62~210.90 μg/mL. The IC50 value of DPPH free radical scavenging capacity was 46.73~68.39 μg/mL. The inhibition rate of pancreatic α-amylase activity in the all groups of dark tea with Pericarpium Citri Reticulatae was less than 30 %. Conclusion: The extract of dark tea with Pericarpium Citri Reticulatae has good antioxidant capacity and in vitro hypoglycemic and lipid-lowering activity, and the addition of volatile oil of Pericarpium Citri Reticulatae can improve the antioxidant, in vitro hypoglycemic and lipid-lowering ability of the extract of dark tea with Pericarpium Citri Reticulatae. This study provides a theoretical basis for the development of health care products related to hypoglycemic, hypolipidemic and antioxidation effects of dark tea with Pericarpium Citri Reticulatae.